FRAME: frame routing and manipulation engine - Pennefather, Sean Niel (Rhodes University, Faculty of Science, Department of Computer Science, 2016)
This research reports on the design and implementation of FRAME: an embedded hardware network processing platform designed to perform network frame manipulation and monitoring. This is possible at line speeds compliant with the IEEE 802.3 Ethernet standard. The system provides frame manipulation functionality to aid in the development and implementation of network testing environments. Platform cost and ease of use are both considered during design resulting in fabrication of hardware and the development of Link, a Domain Specific Language used to create custom applications that are compatible with the platform. Functionality of the resulting platform is shown through conformance testing of designed modules and application examples. Throughput testing showed that the peak throughput achievable by the platform is limited to 86.4 Mbit/s, comparable to commodity 100 Mbit hardware and the total cost of the prototype platform ranged between $220 and $254.
Keywords: Uncatalogued